Beyond the Fourfold Gospel: A Critical Reading of Francis Watson's Gospel Writing: A Canonical Perspective. (December 2014) - Omerzu, Heike
This article discusses Francis Watson's fresh approach to the origins of gospel writing. In general, Watson's attempt to revisit the history of the Synoptic Problem by questioning Q and integrating non-canonical writings is greatly appreciated. Some questions are, however, raised regarding, for instance, the extent to which Luke made use of Matthew or the existence of a Christian 'Sayings Collection' genre. It is argued that an explanation of the Synoptic Problem demands a more complex theory than the one sketched by Watson and that the question of manuscript transmission also needs to be integrated into that theory.